2002
DOI: 10.1080/10550490290087983
|View full text |Cite
|
Sign up to set email alerts
|

Isradipine Enhancement of Cerebral Blood Flow in Abstinent Cocaine Abusers with and without Chronic Perfusion Deficits

Abstract: Nine cocaine abusers with cerebral blood flow (CBF) deficits (hypo-perfused areas) on HMPAO SPECT scans were compared to six without these deficits after six doses of isradipine (5 mg TID). When comparing the scan before isradipine to that after using SPM analysis, the ratio of hypo- to hyper-fusion showed a 16% increase in the maximum Z scores and 30% fewer areas of hypo-perfusion among those cocaine abusers with deficits. These deficits may represent segmental cerebral vasospasm that was reversed by this vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Therefore, the observed antioxidant defense decrease could be due to other origins. Cocaine-induced vasoconstriction may decreases cerebellar blood flow, leading to hypoxia increasing ROS ( Kaufman et al, 1998 ; Gottschalk and Kosten, 2002 ; Pae et al, 2005 ). Additionally, it has been described that cocaine increases brain temperature, which is a reliable indicator of metabolic neural activation ( Kiyatkin and Brown, 2004 ) and thus, cocaine-enhanced metabolism can increase ROS ( Brookes et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed antioxidant defense decrease could be due to other origins. Cocaine-induced vasoconstriction may decreases cerebellar blood flow, leading to hypoxia increasing ROS ( Kaufman et al, 1998 ; Gottschalk and Kosten, 2002 ; Pae et al, 2005 ). Additionally, it has been described that cocaine increases brain temperature, which is a reliable indicator of metabolic neural activation ( Kiyatkin and Brown, 2004 ) and thus, cocaine-enhanced metabolism can increase ROS ( Brookes et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Table III, conflicting results have been reported in preliminary clinical studies examining stimulants' abuse liability in humans [Muntaner et al, 1991;Rosse et al, 1994;Fabian and Silverstone, 1997;Johnson et al, 1999Johnson et al, , 2004Johnson et al, , 2005bMalcolm et al, 1999;Gottschalk and Kosten, 2002;Sofuoglu et al, 2003;Roache et al, 2005]. Roache et al [2005] suggested that isradipine could even increase subjective effects and reinforcement caused by cocaine use.…”
Section: Psychostimulantsmentioning
confidence: 92%
“…In particular, in animals, isradipine showed the greatest anti-ischemic effectiveness in comparison with other calcium-channel antagonists and has been suggested as a therapeutic agent to counteract cocaine-related vasospasm and stroke [Johnson et al, 2001]. Nimodipine not superior to P in reducing craving Rosse et al [1994] Diltiazem 60 mg Pre-treatment with Isradipine attenuated some of the subjective effects and craving for d-amphetamine Johnson et al [1999] Isradipine 15 mg 6 15 cocaine-dependent subjects (6 with CBF deficits, 9 without deficits) and 20 controls OL, SPECT imaging on admission and after 48 h of Isradipine treatment to measure cerebral blood flow Increased CBF in discrete areas Gottschalk and Kosten [2002] Isradipine 10 mg, Naltrexone 50 mg 9…”
Section: Neurodegenerative Disorders Learning and Memorymentioning
confidence: 99%
“…Fourteen healthy normal control subjects were obtained from a database of repeated SPECT scans acquired on different days, as described previously (18,39). Thus in the normal subjects, as in the patients, two scans were obtained for each individual.…”
Section: Methodsmentioning
confidence: 99%